Improving Students’ Reading Comprehension Through Listen Read Discuss (L-R-D) Strategy - Hartanti, Rezkiah; Akib, Muhaiminah; Syarifah, Syarifah (JOLIES : Journal of Linguistic and English Studies, 2025)
The purpose of this research is to find out Listen Read Discussion (L-R-D) strategy increases students’ reading comprehension in English language learning strategies and to know the difference in reading comprehension skills of students who take part in learning using the LRD strategy with students who attend learning without using learning strategies LRD in class VIII at MTs Muhammadiyah 1 in Sorong. The population of this study was all the eighth-grade students at MTs Muhammadiyah 1 Kota Sorong, which consist of two classes A and B. The writer chose purposive sample technique to determine the sample. Therefore, in this study the writer chooses class C as the samples of the research which consists of 20 students. The students will be thought by using LRD as the pre-experiment in order to see the students’ reading comprehension. After that, the students will be divided into five groups consist of five students for each group. The students tested before treatment (pretest) and after treatment (posttest) using reading test to find out the result of LRD method. To get the data score, the writer used SPSS 22.0 to analyze the data statically. The result showed that the process of Listen Read Discussion strategies can improve students’ ability attention, participation, and interest in learning especially in class VIII Mts Muhammadiyah 1 Kota Sorong 2019/2020 showed by statistical calculating data, and the result of the T-Test and T-Table (5.979 > 2.101).